MEDIA LEGO WARNA PADA PENJUMLAHAN BILANGAN BULAT DI SEKOLAH DASAR - Rohmatin, Titik (Elementary School Teacher Education of STKIP Al Hikmah Surabaya, 2019)
This reserach beginning from observation that done by researcher to teaching material of totaling number at State Elementary School of Waung, Krembung, Sidoarjo. On learning process, teacher still have not utilize learning media as a learning source. This study aims to determine the increase in student learning outcomes in integer addition material. This research used class action research design. Data collecting technique that use it, they are observation and test. Data that have collected will be analyzed by using descriptive quantitative analysis technique. Research result showed that by applying colour LEGO media it increased student learning result with classical completeness that obtained on first cycle as big as 64%, second cycle as big as 88%. Beside it, from the research result it also show that there is an improvement on teacher activity on first cycle with percentage as big as 71,15% and on second cycle 95,19%, also improvement on student activity on first cycle with percentage as big as 71,59% and second cycle with percentage 94,89%. Because of that, It was concluded that teaching material of totaling number can be taught by using increase lego colour media.   Keywords: learning result, teaching material of totaling number, colour LEGO media.This reserach beginning from observation that done by researcher to teaching material of totaling number at State Elementary School of Waung, Krembung, Sidoarjo. On learning process, teacher still have not utilize learning media as a learning source. This study aims to determine the increase in student learning outcomes in integer addition material. This research used class action research design. Data collecting technique that use it, they are observation and test. Data that have collected will be analyzed by using descriptive quantitative analysis technique. Research result showed that by applying colour LEGO media it increased student learning result with classical completeness that obtained on first cycle as big as 64%, second cycle as big as 88%. Beside it, from the research result it also show that there is an improvement on teacher activity on first cycle with percentage as big as 71,15% and on second cycle 95,19%, also improvement on student activity on first cycle with percentage as big as 71,59% and second cycle with percentage 94,89%. Because of that, It was concluded that teaching material of totaling number can be taught by using increase lego colour media.   Keywords: learning result, teaching material of totaling number, colour LEGO media.